Local governance and sustainable rural development: Ireland’s experience in an EU context - Cawley, Mary (Journal for Geography, 2009)
This paper discusses the role of local governance partnerships in promoting sustainable rural development with reference to EU policy over the past two decades. Ireland’s experience is presented as an example. From the early 1990s on, new local partnerships associated with both EU and national approaches to rural development compensated for some of the deficiencies of weak local government in Ireland. Partly because of concerns relating to duplication of expenditure and democratic representation, the partnerships have gradually been brought more closely within the remit of the statutory local government structures. Itremains to be seen how Irish rural development policy for 2007-2013 will be implemented within this changing context.